2004
DOI: 10.1111/j.1471-4159.2004.02531.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal A1 receptors mediate increase in extracellular kynurenic acid after local intrastriatal adenosine infusion

Abstract: The naturally occurring purine nucleoside adenosine has pronounced anticonvulsant and neuroprotective properties and plays a neuromodulatory role in the CNS. Kynurenic acid (KYNA) is an astrocyte-derived, endogenous neuroinhibitory compound, which shares several of adenosine's properties. In a first attempt to examine possible interactions between these two biologically active molecules, adenosine was focally applied into the striatum of freely moving rats by reverse microdialysis, and changes in extracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…It therefore seemed sensible to compare the dynamics of our 4 analytes in the lesioned striatum and the contralateral, vehicle-treated striatum using the newly developed methodology. Somewhat surprisingly, in view of the substantial increase in extracellular kynurenic acid and the pronounced activation of several KP enzymes in the lesioned striatum [55,56], extracellular tryptophan, kynurenine and QUIN showed only a modest, non-significant trend towards elevated baseline levels, and extracellular 3-HK remained unmeasurable (Table 1). With the exception of a relatively minor increase in extracellular kynurenine in the lesioned striatum in the first 60-min fraction, extracellular tryptophan, kynurenine and 3-HK levels in the lesioned tissue also did not differ from those measured in the contralateral, PBS-treated striatum after a systemic kynurenine injection (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It therefore seemed sensible to compare the dynamics of our 4 analytes in the lesioned striatum and the contralateral, vehicle-treated striatum using the newly developed methodology. Somewhat surprisingly, in view of the substantial increase in extracellular kynurenic acid and the pronounced activation of several KP enzymes in the lesioned striatum [55,56], extracellular tryptophan, kynurenine and QUIN showed only a modest, non-significant trend towards elevated baseline levels, and extracellular 3-HK remained unmeasurable (Table 1). With the exception of a relatively minor increase in extracellular kynurenine in the lesioned striatum in the first 60-min fraction, extracellular tryptophan, kynurenine and 3-HK levels in the lesioned tissue also did not differ from those measured in the contralateral, PBS-treated striatum after a systemic kynurenine injection (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…During the NAA infusion, a signifi cant increase in the KYNA level (up to 200-300%) was observed, while no change was observed during the infusion of the vehicle (control). Wu et al (2004) reported that the infusion of 5 and 10 mM adenosine caused 1.5-and 2-fold increases in the striatal KYNA level. In addition, they reported that an infusion of 100 μM of the A 1 receptor agonist, N 6 -cyclopentyladenosine, signifi cantly increased the KYNA level.…”
Section: Naa Infusionmentioning
confidence: 99%
“…Since the volume of the sample obtained using MD is usually in the range of 10-30 μL, a highly sensitive analytical method should be employed for the accurate detection of the changes in the neurotransmitter levels in the sample. Several studies on the detection of extracellular KYNA by using MD have been reported (Rassoulpour et al, 1998;Speciale et al, 1990;Wu et al, 2002Wu et al, , 2004Amori et al, 2009b). The striatal KYNA level was found to be increased after the infusion of the naturally occurring nucleoside, adenosine (Wu et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…134 Reverse dialysis of adenosine is capable of raising extracellular kynurenic acid in the rat striatum by interacting with postsynaptic neuronal A1 receptors. 135 Anandamide and arachidonylethanolamine, also known as AEA, are naturally occurring endogenous cannabinoids that are thought to act as neurotransmitters. Giuffrida et al 136 found that anandamide release was increased 8-fold over baseline in the dorsal striatum of freely moving rats after local administration of the D2-like (D2, D3, D4) DA receptor agonist quinpirole, and this response was prevented by the D2-like receptor antagonist raclopride.…”
Section: Other Neurotransmittersmentioning
confidence: 99%